Optimum Design of Phosphorus and Nitrogen Removal from Domestic Wastewater Treatment Plant - Hadi Ghawi, Ali (International Journal of Engineering and Technology, 2018)
In this study, a sewage treatment plant was designed for the city of Al-Nasiriyah in Dhi Qar governorate in southern Iraq serving 316083 inhabitants. The resulting treated water is suitable for agricultural irrigation and can be discharged to the Euphrates River when needed by adding nitrogen and phosphorus removal units to the wastewater treatment plant. The obtained plant design has been verified and optimized by implementing the proposed plant layout in the GPS-X 5.0 modeling and simulation software (Hydromantis). Where the results of the design showed that the total phosphorus flow is higher than the desired limit of 2 mg / L, due to the excessive release during anaerobic digestion. Control of phosphorus concentration can be controlled by adding chemicals (iron or aluminum salts) in different parts of the wastewater treatment plant. In this case, two different control strategies can be implemented: adding aluminum doses in both water and sludge lines (at Chem1 and Chem2 points) or adding aluminum doses in the water line only (at point Chem2). The second strategy showed that it is the most efficient in controlling the concentration of phosphorus and nitrogen produced, which meets the limits of the Iraqi standard of water used in irrigation.Â Â